2018
DOI: 10.21273/hortsci12731-17
|View full text |Cite
|
Sign up to set email alerts
|

Neem Oil Used as a “Complex Mixture” to Improve In Vitro Shoot Proliferation in Olive

Abstract: Shoots of the olive cultivar Moraiolo were previously cultured in aseptic conditions on Olive Medium (OM), with the addition of 4 mg·L−1 of zeatin, 30 g·L−1 of sucrose, and 7 g·L−1 of agar. Then, 1-cm long uninodal explants with two leaves and two axillary buds were excised from the proliferated masses and placed on the same proliferation medium enriched with four concentrations of neem oil (0—control, 0.1, 0.5, and 1.0 mL·L−1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Though the function of nanoparticles depends on their properties and methods of synthesis ( Liu et al., 2020 ), with the application of chemically synthesized ZnO NPs Rao and Shekhawat (2014) reported a dose-dependent significant reduction in shoot length of B. juncea under higher concentrations (1000 and 1500 mg L -1 ). Similarly, other research showed that the addition of ZnO NPs enhanced the growth of Lolium perenne ( Lin and Xing, 2007 ), Allium cepa ( Laware and Raskar, 2014 ), Olea europaea ( Micheli et al., 2018 ), Brassica nigra ( Zafar et al., 2016 ), Cicer arietinum ( Burman et al., 2013 ), Capsicum annuum ( Deore et al., 2010 ), Capsicum annuum ( Datir et al., 2012 ), Zea mays ( Neto et al., 2020 ), Gossypium hirsutum ( Venkatachalam et al., 2017 ), Triticum aestivum ( Munir et al., 2018 ), Brassica oleracea ( Awan et al., 2021 ) and Cucumis sativus ( Zaho et al., 2013 ). In contrast, Chen et al.…”
Section: Resultsmentioning
confidence: 76%
“…Though the function of nanoparticles depends on their properties and methods of synthesis ( Liu et al., 2020 ), with the application of chemically synthesized ZnO NPs Rao and Shekhawat (2014) reported a dose-dependent significant reduction in shoot length of B. juncea under higher concentrations (1000 and 1500 mg L -1 ). Similarly, other research showed that the addition of ZnO NPs enhanced the growth of Lolium perenne ( Lin and Xing, 2007 ), Allium cepa ( Laware and Raskar, 2014 ), Olea europaea ( Micheli et al., 2018 ), Brassica nigra ( Zafar et al., 2016 ), Cicer arietinum ( Burman et al., 2013 ), Capsicum annuum ( Deore et al., 2010 ), Capsicum annuum ( Datir et al., 2012 ), Zea mays ( Neto et al., 2020 ), Gossypium hirsutum ( Venkatachalam et al., 2017 ), Triticum aestivum ( Munir et al., 2018 ), Brassica oleracea ( Awan et al., 2021 ) and Cucumis sativus ( Zaho et al., 2013 ). In contrast, Chen et al.…”
Section: Resultsmentioning
confidence: 76%
“…Olive micropropagation is generally limited due to the strong apical dominance limiting secondary axillary shoot formation [ 32 , 33 ]. Uninodal explants usually produce one shoot; consequently, olive shoot multiplication is performed by segmentation of elongated shoots at each subculture.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is reported in various studies that neem cake in combination with urea can reduce the fertilizer nitrogen requirement [ 30 ]. However, according to a part of the abovementioned paper [ 32 ], the knowledge about the effects of neem oil in in vitro plant culture is still scarce. In this context, the aim of the present work was (i) to study the effect of adding neem oil to proliferation substrates, with reduced zeatin concentrations for olive explants, and (ii) to optimize the rooting phase by using neem oil in different types of substrates.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that 50 ml L -1 coconut water resulted in maximum shooting percentage on monthly basis. Micheli et al, 2018 proved with experimentation that neem oil could also be used for successful intensive proliferation. Moreover, it is a naturally occurring compound and very economical.…”
Section: Shoot Proliferationmentioning
confidence: 99%